Analysing quantitative data : variable-based and case-based approaches to non-experimental datasets - Kent, Raymond A. (New Delhi: SAGE, 2015)
"This innovative book provides a fresh take on quantitative data analysis within the social sciences. Using multidisciplinary non-experimental datasets it demonstrates that data analysis is really an active dialogue between ideas and evidence, between research objectives and data in a dataset." --
Part I. Quantitative data : structure, preparation and analysis approaches : 1. Data structure -- 2. Data preparation -- 3. Approaches to data analysis -- part II. Variable-based analyses : 4. Univariate analysis -- 5. Bivariate analysis -- 6. Multivariate analysis -- part III. Case-based analyses : 7. Set-theoretic methods and configurational data analysis -- 8. Cluster and discriminant analysis -- part IV. Comparing and communicating results : 9. Comparing and mixing methods -- 10. Evaluating hypotheses, explaining and communicating results.
Includes bibliographical references (pages 343-346) and index.
Rasal
Keywords: Quantitative research -- Methodology; Social sciences -- Research -- Methodology; Qualitative research; Methodologie; Quantitative Methode